2016
DOI: 10.1177/1533034616666998
|View full text |Cite
|
Sign up to set email alerts
|

A Systematic Analysis of 2 Monoisocentric Techniques for the Treatment of Multiple Brain Metastases

Abstract: For the planning of multiple brain lesions to be treated with stereotactic radiosurgery, Multiple Metastases Element planning software produced equivalent conformity, homogeneity, dose falloff, and brain V but required significantly lower monitor units, when compared to RapidArc plans.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
25
0
4

Year Published

2018
2018
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 22 publications
(33 citation statements)
references
References 19 publications
4
25
0
4
Order By: Relevance
“…Another study by Narayanasamy et al 25 compared 8 patients (40 targets) and concluded that the 2 techniques achieved comparable CI scores, V 12Gy (cm 3 ), and mean brain dose. However, limited case numbers likely provided insufficient power to detect detailed differences between the 2 treatment planning systems.…”
Section: Comparison Of Mean Brain Dose Between Techniquesmentioning
confidence: 99%
“…Another study by Narayanasamy et al 25 compared 8 patients (40 targets) and concluded that the 2 techniques achieved comparable CI scores, V 12Gy (cm 3 ), and mean brain dose. However, limited case numbers likely provided insufficient power to detect detailed differences between the 2 treatment planning systems.…”
Section: Comparison Of Mean Brain Dose Between Techniquesmentioning
confidence: 99%
“…Volumetric modulated arc therapy (VMAT) is commonly employed for SRS treatment delivery. Several studies have demonstrated that multiarc noncoplanar VMAT can deliver highly conformal plans to the target(s) and spare adjacent critical structures . More recently, single‐isocenter VMAT‐SRS treatment techniques were introduced for dose delivery to multiple intracranial targets/lesions concurrently, with the latter being an attractive approach since treatment duration can be further reduced without necessarily compromising plan quality .…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have demonstrated that multiarc noncoplanar VMAT can deliver highly conformal plans to the target(s) and spare adjacent critical structures. [9][10][11][12][13][14][15][16] More recently, single-isocenter VMAT-SRS treatment techniques were introduced for dose delivery to multiple intracranial targets/lesions concurrently, with the latter being an attractive approach since treatment duration can be further reduced without necessarily compromising plan quality. [17][18][19] A single isocenter has been found sufficient for VMAT-SRS of multiple intracranial metastases, whereas minor improvements in plan quality can be achieved when additional isocenter(s) are used.…”
Section: Introductionmentioning
confidence: 99%
“…This concept differs from other conformal techniques such as that employed in Brainlab's Multiple Metastases Element (MME) (Brainlab AG, Munich, Germany), which offers treatment of a subset of targets within a given arc. MME selects the optimal number of arcs based on the number and location of the targets but does not vary which targets are treated between control points within an arc …”
Section: Introductionmentioning
confidence: 99%
“…MME selects the optimal number of arcs based on the number and location of the targets but does not vary which targets are treated between control points within an arc. 6 This study aims to design a system that uses simulated annealing to optimize the collimation of subsets of targets at specified control points, through a process defined as intraarc binary collimation (iABC), along with control point-specific MU weighting, to achieve prescription target coverage and normal tissue sparing, where this would be normally accomplished through MLC modulation in a VMAT plan.…”
Section: Introductionmentioning
confidence: 99%